The Mechanisms and Functions of GDF‐5 in Intervertebral Disc Degeneration. Issue 3 (4th April 2021) - Guo, Sheng; Cui, Liqiang; Xiao, Changming; Wang, Chenglong; Zhu, Bin; Liu, Xueli; Li, Yujie; Liu, Xinyue; Wang, Dingxuan; Li, Sen
Abstract : Intervertebral disc degeneration (IDD) is widely recognized as the main cause of low back pain, which leads to disability in aging populations and induces great losses both socially and economically worldwide. Unfortunately, current treatments for IDD are aimed at relieving symptoms instead of preserving disc structure and function. Researchers are forged to find new promising biological therapeutics to stop, and even reverse, IVD degeneration. Recently, the injection of growth factors has been shown to be a promising biological therapy for IDD. A number of growth factors have been investigated to modulate the synthesis of the extracellular matrix (ECM) through a variety of pathogenetic biological mechanisms, including suppressing inflammatory process and down‐regulating degrading enzymes. However, growth factors, including Transforming Growth Factor‐β (TGF‐β), Fibroblast Growth Factor (FGF), and Insulin‐like Growth Factor‐1 (IGF‐1), may induce unwanted blood vessel in‐growth, which accelerates the process of IDD. On the contrary, studies have demonstrated that injection of GDF‐5 into the intervertebral disc of mice can effectively alleviate the degeneration of the intervertebral disc, which elicits their response via BMPRII and will not induce blood vessel in‐growth. This finding suggests that GDF‐5 is more suitable for use in IDD treatment compared with the three other growth factors. Substantial evidence has suggested that GDF‐5 may maintain the structure and function of the intervertebral disc (IVD). GDF‐5 plays an important role in IDD and is a very promising therapeutic agent for IDD. This review is focused on the mechanisms and functions of GDF‐5 in IDD. Abstract : The nutritional supplies of inner AF and NP occur mainly through the endplate pathway. The normal endplate contains proteoglycan, collagen, and water, which will decrease substantially in the degenerated endplate. As the arrows show, all nutrients can pass through the normal cartilage endplate. When the endplate degenerates, passing nutrients are greatly reduced. After an injection of GDF‐5, there may be an increase in the delivery of nutrients.